Comparison of high-intensity vs. high-volume resistance training on the BDNF response to exercise - Church, D. D.; Hoffman, J. R.; Mangine, G. T.; Jajtner, A. R.; Townsend, J. R.; Beyer, K. S.; Wang, R.; La Monica, M. B.; Fukuda, D. H.; Stout, J. R. (Journal of Applied Psychology, 2016)
This study compared the acute and chronic response of circulating plasma brain-derived neurotrophic factor (BDNF) to high-intensity low-volume (HI) and low-intensity high volume (HV) resistance training. Twenty experienced resistance-trained men (23.5 ± 2.6 y, 1.79 ± 0.05 m, 75.7 ± 13.8 kg) volunteered for this study. Before the resistance training program (PRE), participants performed an acute bout of exercise using either the HI [3-5 reps; 90% of one repetition maximum (1RM)] or HV (10-12 reps; 70% 1RM) training paradigm. The acute exercise protocol was repeated after 7 wk of training (POST). Blood samples were obtained at rest (BL), immediately (IP), 30 min (30P), and 60 min (60P) post exercise at PRE and POST. A three-way repeated measure ANOVA was used to analyze acute changes in BDNF concentrations during HI and HV resistance exercise and the effect of 7 wk of training. No training × time × group interaction in BDNF was noted (P = 0.994). Significant main effects for training (P = 0.050) and time (P < 0.001) in BDNF were observed. Significant elevations in BDNF concentrations were seen from BL at IP (P = 0.001), 30P (P < 0.001), and 60P (P < 0.001) in both HI and HV combined during PRE and POST. BDNF concentrations were also observed to increase from PRE to POST when collapsed across groups and time. No significant group × training interaction (P = 0.342), training (P = 0.105), or group (P = 0.238) effect were noted in the BDNF area under the curve response. Results indicate that BDNF concentrations are increased after an acute bout of resistance exercise, regardless of training paradigm, and are further increased during a 7-wk training program in experienced lifters.